Political party formation by former armed opposition groups after civil war. Issue 6 (18th September 2016) - Manning, Carrie; Smith, Ian
ABSTRACT: Under what conditions are rebel groups successfully incorporated into democratic politics when civil war ends? Using an original cross-national, longitudinal dataset, we examine political party formation by armed opposition groups over a 20-year period, from 1990 to 2009. We find that former armed opposition groups form parties in more than half of our observations. A rebel group's pre-war political experience, characteristics of the war and how it ended outweigh factors such as the country's political and economic traits and history. We advance a theoretical framework based on rebel leaders' expectations of success in post-war politics, and we argue that high rates of party formation by former armed opposition groups are likely a reflection of democratic weakness rather than democratic robustness in countries emerging from conflict.